West Antarctic Ice Sheet Dynamics in the Amundsen Sea Sector since the Late Miocene—Tying IODP Expedition 379 Results to Seismic Data - Gille-Petzoldt, Johanna; Gohl, Karsten; Uenzelmann-Neben, Gabriele; Grützner, Jens; Klages, Johann P.; , IODP Expedition 379 Scientists; Bauersachs, T.; Courtillat, M.; Cowan, E.; De Lira Mota, M.; Esteves, M.; Fegyveresi, J.; et al. (Frontiers in Earth Science, 2022)
Observations of rapid ongoing grounding line retreat, ice shelf thinning and accelerated ice flow from the West Antarctic Ice Sheet (WAIS) may forebode a possible collapse if global temperatures continue to increase. Understanding and reconstructing WAIS dynamics in past warmer-than-present times will inform about its behavior as an analogue for future climate scenarios. International Ocean Discovery Program (IODP) Expedition 379 visited the Amundsen Sea sector of Antarctica to obtain geological records suitable for this purpose. During the expedition, cores from two drill sites at the Resolution Drift on the continental rise returned sediments whose deposition was possibly influenced by WAIS dynamics from late Miocene to Holocene times. To examine the WAIS dynamics, shipboard physical properties and sedimentological data are correlated with seismic data and extrapolated across the Resolution Drift into the extended region via core-log seismic integration. An interval with strongly variable physical properties, high diatom abundance and ice-rafted debris occurrence, correlating with partially high amplitude seismic reflection characteristics was identified between 4.2 and 3.2 Ma. Sedimentation during this interval is interpreted as having occurred during an extended warm period with a dynamic WAIS in the Amundsen Sea sector. These records compare to those of other drill sites in the Ross Sea and the Bellingshausen Sea, and thus suggest an almost simultaneous occurrence of extended warm periods in all three locations.